Estrategias de gestión turísticas para el desarrollo del turismo rural en el humedal abras de mantequilla. - Pezo Escobar, Selena María Del (2021)
The Abras de Mantequilla wetland has a great potential for flora and fauna, in which rural tourism activities can be developed, such as hiking, bird watching, canoe rides, which is interesting for tourists who seek to relax in a environment different from the noise and pollution of the city. Through the implementation of tourism management strategies, what is sought is the innovation of new activities to attract more tourists to the wetland, since the wetland consists of 22,500 hectares which must be used for tourism for the benefit of the community. Through this case study, the tourist promotion of the Abras de Mantequilla wetland is sought for the development of rural tourism in the site